Bulk crystal growth and characterization of the bismuth ferrite-based material Bi3FeO4(MoO4)2. Issue 15 (14th March 2019) - Li, Conggang; Gao, Zeliang; Tian, Xiangxin; Zhang, Junjie; Ju, Dianxing; Wu, Qian; Lu, Weiqun; Sun, Youxuan; Cui, Deliang; Tao, Xutang
Abstract : The large, high-quality Bi3 FeO4 (MoO4 )2 single crystals of size up to 28 × 20 × 12 mm 3 were grown successfully by the TSSG method. The thermal, optical, magnetization, and polarized Raman properties are investigated in detail. Abstract : High-quality single crystals of the bismuth ferrite-based material Bi3 FeO4 (MoO4 )2 of size up to 28 × 20 × 12 mm 3 were successfully grown via the modified top-seeded solution growth (TSSG) technique by using MoO3 –Bi2 O3 as the self-flux. Bi3 FeO4 (MoO4 )2 crystallizes into the space group C 2/ c (no. 15, a = 16.927(12) Å, b = 11.672(12) Å, c = 5.263(4) Å, and Z = 4) with a typical scheelite-type structure. The as-grown crystals exhibit major face forms {100}, {110}, and {111}, which is consistent with the predicted growth morphology on the basis of the BFDH method. The high-resolution X-ray diffraction results demonstrate that the FWHM of the (200) face of the crystal is 31 arcsec, which indicates a high quality. The thermal measurements showed that the crystal melts incongruently and is thermally stable up to 912 °C. The crystal also displays a wide transmission region of 0.64–5.8 μm with a band gap of 2.26 eV. Moreover, the magnetization properties with variations in temperature were measured, and the anti-ferromagnetic ordering is found to occur at 11 K. Notably, the Raman scattering measurements show that the crystal exhibits an intense Raman shift and narrow line-width that are comparable with those of the YVO4 crystal. In addition, the first-principles calculations on the title compound were carried out to analyze the structure–property relationships. These results of the Bi3 FeO4 (MoO4 )2 single crystals may provide a better understanding for further studies of these materials.